Adverse reactions during treatment with amiodarone hydrochloride. Issue 6386 (16th July 1983) - McGovern, B; Garan, H; Kelly, E; Ruskin, J N
Abstract : Amiodarone was administered to 80 patients with recurrent cardiac tachyarrhythmias previously resistant to drug treatment. Forty nine patients were treated for ventricular tachycardia or fibrillation and 31 for supra-ventricular arrhythmias. The mean (range six days to 51 months), permitting a total of 100 patient years of observation. Adverse reactions were observed in 69 patients. Severe side effects were encountered in 13: four patients developed interstitial pneumonitis, four patients developed incessant ventricular tachycardia, three patients taking amiodarone and digoxin sustained sinus node arrest with depression of escape foci, one patient developed hepatitis, and one patient developed hypercalcaemia with renal failure. Furthermore, a rise in the serum concentration of digoxin and potentiation of warfarin anticoagulation occurred in cases in which these agents were combined with amiodarone. Amiodarone was stopped in 14 patients because of side effects. Although amiodarone is effective in suppressing arrhythmias in most patients in whom extensive use of antiarrhythmic drugs has been unsuccessful, it is associated with diverse and serious toxicity. These observations suggest that at present the use of amiodarone should be reserved for patients with life threatening or seriously disabling arrhythmias in whom longer established drugs have been ineffective or are contraindicated.